Performance, Carcass Characteristics, and Meat Quality of Broiler Chickens Fed β-Mannanase and Two Levels of Energy - Jalal, M. A. R.; Zakaria, H. A. H.; Hayajneh, F. M.; Mehyar, G. M. (Tropical Animal Science Journal, 2023)
This study aimed at evaluating the response to supplementation of β-Mannanase with two levels of energy on performance, carcass yield, and meat quality of 1600 1-d-old straight run Indian River broilers which were randomly allotted to 4 dietary treatments (10 replicates/treatment, 40 chicks per replicate) in a 35-d feeding trial. The trial consisted of 2 phases, starter (0 to 14 d) and grower (15 to 35 d). The experiment was designed in a 2 x 2 factorial arrangement. The first factor was the energy level of the ration consisted of 2 levels, i.e., a low energy level with 2.900 kcal ME/kg during the starter phase and 3.000 kcal ME/kg during the grower phase; and a normal energy level with 3020 kcal ME/kg during starter phase and 3120 kcal ME/kg during grower phase, with variations based on the content of feed grade soybean oil. The second factor was the level of β-Mannanase in the diet consisted of 2 levels, i.e., ration without β-Mannanase (BETAMINUS: 0%) and ration with 0.05% β-Mannanase (BETAPLUS: 0.05%). Feeding low ME increased feed intake (p